Effect of Alkynyl Group on Reactivity in Photoaffinity Labeling with 2‐Thienyl‐Substituted α‐Ketoamide. Issue 11 (31st January 2022) - Moriyama, Takahiro; Mizukami, Daiki; Yoritate, Makoto; Usui, Kazuteru; Takahashi, Daisuke; Ota, Eisuke; Sodeoka, Mikiko; Ueda, Tadashi; Karasawa, Satoru; Hirai, Go
Abstract: Minimalist photo‐reactive probes, which consist of a photo‐reactive group and a tag for detection of target proteins, are useful tools in chemical biology. Although several diazirine‐based and aryl azide‐based minimalist probes are available, no keto‐based minimalist probe has yet been reported. Here we describe minimalist probes based on a 2‐thienyl‐substituted α‐ketoamide bearing an alkyne group on the thiophene ring. The 3‐alkyne probe showed the highest photo‐affinity labeling efficiency. Abstract : Keeping it simple : Minimalist photo‐reactive probes, consisting of a photo‐reactive group and a tag for the detection of target proteins, are useful tools in chemical biology. We have synthesized minimalist probes based on 2‐thienyl‐substituted α‐ketoamide by introducing an alkyne group into the thiophene ring. The position of the alkyne moiety significantly influences the reactivity.